Analysis of Problematic Financing in Murabahah Contract Products of Cooperative Members in an Islamic Perspective: Case Study of Koperasi Swadaya Pribumi - Muhammad Akmal; Abdurrahim Abdurrahim; Mochammad Rizqi Nur Syam Badri; Ahmad Nuh (Economics and Digital Business Review, 2025)
Financing distribution with murabahah contract in Islamic cooperatives is the main instrument in supporting the needs of members, but often faces problematic financing that disrupts financial stability and member trust. This study uses a case study method with a qualitative descriptive approach in the Swadaya Pribumi Cooperative to analyze the causes of problematic financing and solutions to overcome them from an Islamic economic perspective. The results of the study indicate that the main factors causing problematic financing are inadequate feasibility analysis, weak post-contract supervision, and low member discipline. The solutions offered include the application of the principles of ta'awun, syura, and justice, as well as strengthening risk management and Islamic financial literacy among members